Pengaruh Terapi Meditasi (Dzikir) terhadap Tingkat Stres pada Lansia - Sutioningsih, Suci; Suniawati, Sri; Hamsanikeda, Suhuda (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2019)
Stress is a condition which produced by an environment alteration which received as a case challenging, threatening or damaging the equilibrium or dynamic state of a person. Stress experienced by humans can be derived from various sources from within of a person, family, and environment. On an elderly is not uncommon that stress can often occur. To overcome and relieve a stress, there are several ways can be do such as gymnastics, reflection, laughter therapy, aromatherapy, and meditation. The purpose of this study was to find out the meditation therapy (dzikir) effect to the stress levels of elderly. This study uses the analytical method with a One-Group Pre-Test-Posttest Design. The sampling method used is purposive sampling. Population use all elderly at the Mojopahit Elderly Institution of Mojokerto at 2012 with a sample of 20 respondents, the data obtained from the dissemination of questionnaires. The result of the respondents study included to the middle criteria are about 2 people (10%) and the low criteria are about 18 people (90%). In the data analysis, researcher use a t-test with the provisions of p<a ( p=0.015; a=0.05). From the result of research known p=0.015 < 0.05, its mean there is an effect of meditation therapy (dzikir) implementation to the stress levels of elderly. So the meditation therapy (dzikir) should be applied at the elderly institution as a daily activity for the elderly, especially to relieve a stress. Keywords : stress, meditation therapy, elderly